A NUMERICAL ANALYSIS OF THE ELECTRICAL OUTPUT RESPONSE OF A NONLINEAR PIEZOELECTRIC OSCILLATOR SUBJECTED TO A HARMONIC AND RANDOM EXCITATION - Pereira, Tiago Leite; Paula, Aline Souza de; Fabro, Adriano Todorovic; Savi, Marcelo Amorim (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The renewable energy is in the focus of many researches in the last decades, and the use of piezoelectric material can be used to obtain one source of this renewable energy. In this case, energy harvesting explores mainly the source of ambient motion and the piezoelectric material convert mechanical energy, present in the ambient motion, into electrical energy. In the work, we present a nonlinear bistable piezomagnetoelastic structure subjected to harmonic and random base excitation. At first, harmonic excitation is of concern and then, the system subjected to random excitation is analyzed. The goal of the numerical analysis is to present an investigation of the best electrical output response of the system given harmonic and random excitations.